Fresno County Bar Association Witkin Luncheon at Hilton Hotel with Bernard Witkin - Watkins, Howard::::::::: (1986)
Bernard Witkin at lectern talking about recent U.S. Supreme Court decisions; seated: Judge James V. Paige and Fresno County Bar Association President Judy Soley